Species-dependent wiring of jasmonate signalling determines pine defence efficiency against Bursaphelenchus xylophilus - Adrián López-Villamor; Marta Nunes da Silva; Victoria Pastor; Marta W. Vasconcelos (Journal of Pest Science, 2026)
Pine wilt disease, caused by the pinewood nematode Bursaphelenchus xylophilus , poses a serious threat to pine forests worldwide, yet the hormonal and metabolic mechanisms that determine whether a pine species succumbs to or tolerates infection remain poorly understood. Jasmonic acid (JA) signalling is a central defence pathway in plants, but its precise contribution to species-dependent resistance in Pinus has not been systematically evaluated. This study dissects how targeted activation and inhibition of the JA signalling pathway remodel defence responses and nematode infection dynamics in three pine species with contrasting susceptibility to the pathogen (from most to least susceptible, Pinus pinaster , P. pinea , and P. taeda ). Seedlings were treated with methyl jasmonate (MeJA) or the jasmonate inhibitor sodium diethyldithiocarbamate (DIECA) before nematode inoculation, and effects on symptom development, nematode colonisation, primary and secondary metabolism, oxidative stress, phytohormone profiles, and defence-related gene expression were assessed. P. pinaster developed clear symptoms and a marked increase in nematode numbers, whereas P. pinea and P. taeda remained largely asymptomatic. In P. pinaster , MeJA reduced both symptom severity and nematode proliferation, while DIECA impaired early defence activation although a delayed compensatory response was detectable. Across species, nematode infection triggered significant increases in phenolic compounds, flavonoids, and carotenoids, particularly in P. pinea , highlighting the contribution of secondary metabolism to plant resistance to the pinewood nematode. Overall, untreated infected plants showed higher lipid peroxidation compared with MeJA-treated, and phytohormone analyses revealed species-specific regulatory patterns. Gene expression patterns confirmed activation of phenylpropanoid and terpenoid pathways, with PAL , GGPPS , and MYC2 showing species- and treatment-specific regulation. Together, these results are consistent with the existence of distinct regulatory architectures underlying susceptibility versus tolerance, and provide hormonal, metabolic, and transcriptional profiles that may inform future breeding and priming strategies against pine wilt disease, though further functional validation will be needed to establish causation.